Sustainable Ecotourism Development In Negeri Lumoli, Maluku-Indonesia: Sociology Studies - Elsina Titaley (UIN Sunan Gunung Djati, 2023)
The potential development of the tourism sector is often associated with its role as one of the strengths of the source of income contribution to regional income. Sociologically, Maluku consists of a series of large and small islands with various beauties, makes Maluku an amazing tourist place in cultural customs and natural scenery. In this context, tourism development must refer to sustainable tourism development in Negeri Lumoli, Maluku-Indonesia, which has good tourism and culture. This research aimed to explain how to develop waterfalls as Ecotourism for sustainable tourism development in Negeri Lumoli. Sustainable tourism development refers to the World Tourism Organization, which includes environmentally, economically, and socio-culturally sustainable components. One form of sustainable tourism is Ecotourism. The tourism process is carried out by protecting and minimizing environmental impacts, maximizing benefits for residents, and maximizing tourist satisfaction. The development of an area into an ecotourism area will foster hope in the community so that Ecotourism can positively influence people's lives and the living environment. In this ecotourism research conducted in Negeri Lumoli, related to the existence of waterfalls, the results of the study indicate that community expectations from ecotourism development can support three important components of the community's economy, ecology that is still maintained, and socio-cultural sustainability, so that in the end it becomes a destination for tourism. Superior and sustainable tourism.Â